Enhanced efficiency of cell death by lysosome-specific photodamage - Tayana Mazin Tsubone (Nature Portfolio, 2017)
Abstract Mobilization of specific mechanisms of regulated cell death is a promising alternative to treat challenging illness such as neurodegenerative disease and cancer. The use of light to activate these mechanisms may provide a route for target-specific therapies. Two asymmetric porphyrins with opposite charges, the negatively charged TPPS2a and the positively charged CisDiMPyP were compared in terms of their properties in membrane mimics and in cells. CisDiMPyP interacts to a larger extent with model membranes and with cells than TPPS2a, due to a favorable electrostatic interaction. CisDiMPyP is also more effective than TPPS2a in damaging membranes. Surprisingly, TPPS2a is more efficient in causing photoinduced cell death. The lethal concentration on cell viability of 50% (LC50) found for TPPS2a was ~3.5 (raw data) and ~5 (considering photosensitizer incorporation) times smaller than for CisDiMPyP. CisDiMPyP damaged mainly mitochondria and triggered short-term phototoxicity by necro-apoptotic cell death. Photoexcitation of TPPS2a promotes mainly lysosomal damage leading to autophagy-associated cell death. Our data shows that an exact damage in lysosome is more effective to diminish proliferation of HeLa cells than a similar damage in mitochondria. Precisely targeting organelles and specifically triggering regulated cell death mechanisms shall help in the development of new organelle-target therapies.